Pengaruh Pemberian Pupuk PWR Nutrition Terhadap Intensitas Serangan Hama Pada Budidaya Kacang Tanah (Arachis hypogaea L.) - Muhammad Arifin; Nurlaila Nurlaila; Tuti Heiriyani (Universitas Lambung Mangkurat, 2026)
Peanut is an important agricultural commodity in Indonesia due to its high economic value. However, the excessive use of inorganic fertilizers in peanut cultivation may adversely affect soil quality and increase plant susceptibility to pest infestations. One such organic fertilizer is Power Nutrition, which resistance mechanisms. This study aimed to evaluate the effect of Power Nutrition fertilizer application on pest attack intensity in peanut cultivation and to determine the most effective application frequency for reducing pest damage. The experiment was arranged in a Randomized Block Design with a single factor, namely the frequency of Power Nutrition application. Five treatments were tested: p0 (without Power Nutrition), p1 (one application at 5 weeks after planting), p2 (two applications at 5 and 7 weeks after planting), p3 (three applications at 5, 7, and 9 weeks after planting), and p4 (four applications at 5, 7, 9, and 11 weeks after planting). Each treatment was replicated four times, resulting in 20 experimental units. The observed parameters included the identification of pest insect species and the intensity of pest attacks. A total of 1,297 insect individuals were recorded in the peanut field, representing 8 orders, 26 families, 31 genera, and 31 species. The results indicated that Power Nutrition application significantly influenced pest attack intensity. Treatment p4 consistently produced the lowest pest attack intensity, averaging approximately 1% between 7 and 11 weeks after planting. This reduction was likely associated with improved plant vigor, environmental conditions, and lower pest population pressure within the peanut cultivation system.